2020
DOI: 10.1021/acs.est.0c03800
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Pd-Loaded Ti4O7 Electrode for Direct Anodic Destruction of Perfluorooctanoic Acid

Abstract: We here present a novel Ti 4 O 7 -based electrode loaded with amorphous Pd clusters that achieve efficient anodic destruction of perfluorooctanoic acid (PFOA), a persistent water pollutant with significant environmental and human health concerns. These amorphous Pd clusters were characterized by the disordered, noncrystalline arrangement of Pd single atoms in close proximity, in contrast to crystalline Pd nanoparticles that have been often employed to tailor the electronic properties of an electrode. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 79 publications
0
54
1
Order By: Relevance
“…Since hydrodefluorination cannot be avoided during UV/sulfite treatment, an oxidative post-treatment is usually required to cleave the remaining C–F bonds in H-rich residues. These mechanistic insights will benefit the development and understanding of PFAS treatment technologies such as photochemical degradation in homogeneous and heterogeneous systems, electrochemical degradation, and plasma treatment, where reductive and/or oxidative processes are involved. The HO • oxidation results also provide data to compare with similar reaction systems , and achieve a deeper mechanistic understanding.…”
Section: Resultsmentioning
confidence: 99%
“…Since hydrodefluorination cannot be avoided during UV/sulfite treatment, an oxidative post-treatment is usually required to cleave the remaining C–F bonds in H-rich residues. These mechanistic insights will benefit the development and understanding of PFAS treatment technologies such as photochemical degradation in homogeneous and heterogeneous systems, electrochemical degradation, and plasma treatment, where reductive and/or oxidative processes are involved. The HO • oxidation results also provide data to compare with similar reaction systems , and achieve a deeper mechanistic understanding.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3c, the pre‐edge energy of the Pd (K‐edge) XANES spectrum for Pd/MoO 3‐x features a obvious shift to higher energy, revealing the positive oxidation state of Pd, compared with that of Pd foil (Pd valance state of zero) [20] . Fourier transform R‐space curves of the Pd K‐edge EXAFS spectra (Figure 3d) show that, one prominent peak exists, centered at 2.5 Å from the Pd−Pd contribution in Pd foil.…”
Section: Resultsmentioning
confidence: 94%
“…PFOA is chemically stable and is resistant to many traditional techniques due to its strong C–F bond and high oxidation potential, but recently electrochemical oxidation has been proved to be an effective method for degrading PFOA in an aqueous solution. 3,52 The electrochemical oxidation reactivity of the Ti/RuO 2 –IrO 2 @Pt electrode to PFOA was evaluated in this research, as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, electrochemical oxidation technology has attracted great attention in wastewater purification applications, and as a versatile approach it is frequently used to degrade recalcitrant and toxic organic pollutants, especially perfluorinated compounds. 1–4 The electrode material is the key to optimizing the electrochemical oxidation processes, which directly affects the oxidation efficiency, reaction mechanism, and mineralization degree of organic pollutants on the electrode surface. 5,6 An ideal anode material should have several properties: (i) high electrocatalytic activity for degrading organic pollutants, (ii) high stability under anodic polarization conditions, and (iii) low manufacturing cost and long service lifetime.…”
Section: Introductionmentioning
confidence: 99%